Understanding Intercultural Encounters: Communication Practices of Bugis and Ternate People in Ternate - Badruddin `Kaddas; Rakhmat Rakhmat; Aisyiyah Hanif Mualim (Universitas Darussalam Gontor, 2025)
This study aims to probe and comprehend the dynamics of communication between The Bugis and Ternate people in the context of daily life in Ternate. Communication between strangers and host cultures often presents complex and interesting challenges in understanding different cultures, beliefs and social practices. This study used a qualitative approach using intimate interviews and participant observation to gain in-depth insight into the communication experiences between the Bugis and Ternate people. Research participants consisted of Bugis individuals living in Ternate and Ternate people who had direct interactions with them. The results of the research provides a better understanding of how The Bugis as strangers and Ternate people as host cultures communicate, the challenges they face in establishing intercultural relations, and the strategies and mechanisms used to overcome these differences. This research also found the importance of intercultural communication competence and the important role of language, nonverbal expression, and full understanding of certain cultural perceptions. The researcher trusts that the research will make an important contribution to cross-cultural understanding and intercultural communication, as well as provide practical suggestions for enhancing understanding and relations between the Bugis and Ternate people in Ternate. This research also can be a basis for further research on intercultural communication in Indonesia and involving other cultural groups.